KESALAHAN BERBAHASA PADA MEDIA ONLINE METROJAMBI.COM RUBRIK PERISTIWA TERBITAN AGUSTUS 2025 - Nurmalini; Agus Setyonegoro; Hilman Yusra; Ade Kusmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to describe the forms and explain how to correct language errors in the online news media MetroJambi.com, the events section published in August 2025. Errors in language use can lead to ambiguity and misinterpretation in conveying information to the public. The method used in this study is descriptive qualitative, with documentation and note-taking techniques. Words, phrases, and sentences from the news media MetroJambi.com, the events section published in August 2025, constitute the data in this study. The data for these words, phrases, and sentences were obtained from regional news articles in the MetroJambi.com events section published in August 2025. The results of the study indicate language errors at four levels: spelling, morphology, syntax, and semantics. There were 130 errors in spelling, 109 errors in morphology, 133 errors in syntax, and 129 errors in semantics.